Adoption of Improved Mungbean Production Technologies in Selected East African Countries - Mmbando, Frank; Mbeyagala, Emmanuel; Binagwa, Papias; Karimi, Rael; Opie, Hellen; Ochieng, Justus; Mutuoki, Tarcisius; Nair, Ramakrishnan Madhavan (Agriculture, 2021)
This study analyzes the factors that influence the probability and extent of the adoption of mungbean production technologies in Tanzania, Kenya and Uganda, using multivariate probit and Poisson regression models. The results show that the probability and extent of the adoption of mungbean production technologies are influenced by gender of the household, household size, farm size, livestock size, household assets, access to extension services and access to credit. The study suggests that policy interventions that aimed at targeting women farmers, increasing household asset and information dissemination, such as field demonstrations and training programs, are crucial in enhancing technology adoption among smallholder farmers.
Keywords: adoption; mungbean; production technologies; multivariate probit; poisson regression; East Africa